Age Estimation from Human Skins by Using AgNOR - Isır, Aysun Baransel; Bakır, Kemal; Uçak, Ramazan; Dülger, Hikmet Ergin (Fırat University, 2004)
Objective: The age estimation of postmortem diagnosis is a considerable problem in forensic issues. For age estimation, numerical methods that are evaluated according to proliferative activity of normal cells are tested. AgNOR was exceptionally applied for estimation of chronological ages of unidentified individuals in this study. Use of this method for forensic purposes is presented as an alternative method to determine the age of an individual. Some difficulties seen in the other methods used in routines tried to overcome. Method: In this study, mitotic activity was examined by AgNOR method that was based on silver-staining of nucleolus organizer regions (NORs), and avarage proliferative index was obtained. These index datas were related eachother according to age groups. Results: The study was conducted on 38 postmortem samples (23 males and 15 females) without any tumoral pathology in their past. Samples were divided into four age groups; which were newborns (0-12 months), infants (ages of 1-5), adults (ages of 25-35), and olds (ages of 50 and above). When a brief investigation was performed with AgNOR staining, age-related changes were certainly determined and were found a statistically significant correlation (p

Amaç: Özellikle kimlik tespiti yapılamamış postmortem örneklerden, yaş tespiti yapılması adli tıp için henüz netlik ve pratik uygulamada kolaylık gösterememiş, oldukça önemli bir problem olmaya devam etmektedir. Bu amaçla normal hücrelerin proliferatif aktivitesine göre degerlendirilen kantitatif metodlar denenmektedir. Biz de çalışmamızda AgNOR boyama yöntemi ile insan epidermisinden alınan küçük doku örnekleri ile özellikle kimligi belirlenememiş postmortem olgularda yaş tespitinin yapılabilirligini göstermeyi amaçladık. Gereç ve Yöntem: Bu çalışmada mitotik aktivite, nükleolar organize edici bölgelerin gümüşle boyanması esasına dayalı AgNOR yöntemiyle incelendi ve ortalama proliferatif indeks elde edildi. Bu indekse baglı AgNOR dagılımları skoru yaş gruplarına göre ilişkilendirildi. Bulgular: Çalışmaya geçmişinde herhangi bir tümoral hastalık hikayesi olmadıgı ögrenilen postmortem örneklerin toplandıgı, yeni dogan (0-12 ay), infant (1-5 yaş), erişkin (25-35 yaş), 50 yaş ve üzeri olmak üzere 23 Erkek (E), 15 Kadın (K) toplam 38 olgudan 4 yaş grubu oluşturuldu. Yaş gruplarına göre AgNOR dagılım skorları arasında fark saptandı ve istatistiksel olarak anlamlı korelasyon bulundu (p
AgNOR Yöntemi ile Insan Epidermisinden Yaş Tespiti